ECOLOGICAL COMPENSATION IN URBAN DESIGN OF COASTAL LOWLAND CITY: LINCHENG NEW TOWN - K. Wang; Z. Cao; L. Xu (Lowland Technology International, 2005)
The ecological problem of living environment should be explored to the city extension. Urban design is working at control on the physical form and environments of a town and managing its multi systems. Accordingly, it is with great necessity to emphasize the operation of ecological compensation through out the whole process of urban design. It is especially demanded in the coastal lowland cities in China, which are developing most quickly and breaking the balance of nature most seriously. This paper tries to study four dominating factors (landscape, water system, green space, buildings) of ecological control and compensation in urban design through a serious of urban design projects in Lincheng New Town with consideration of the ecological character of coastal cities.